Violympic toán 8

TL

Tìm x, biết:

a, \(3x\left(x-2\right)-x+2=0\)

b, \(x^2+5x+4=0\)

PT
16 tháng 11 2017 lúc 19:49

a) \(3x\left(x-2\right)-x+2=0\)

\(3x\left(x-2\right)-\left(x-2\right)=0\)

\(\left(x-2\right)\left(3x-1\right)=0\)

\(\Rightarrow\left[{}\begin{matrix}x-2=0\\3x-1=0\end{matrix}\right.\)

\(\Rightarrow\left[{}\begin{matrix}x=2\\x=\dfrac{1}{3}\end{matrix}\right.\)

b) \(x^2+5x+4=0\)

\(x^2+x+4x+4=0\)

\(x\left(x+1\right)+4\left(x+1\right)=0\)

\(\left(x+1\right)\left(x+4\right)=0\)

\(\Rightarrow\left[{}\begin{matrix}x+1=0\\x+4=0\end{matrix}\right.\)

\(\Rightarrow\left[{}\begin{matrix}x=-1\\x=-4\end{matrix}\right.\)

Bình luận (0)
LG
16 tháng 11 2017 lúc 19:49

\(a,3x\left(x-2\right)-x+2=0\)

\(\Rightarrow3x\left(x-2\right)-\left(x-2\right)=0\)

\(\Rightarrow\left(x-2\right)\left(3x-1\right)=0\)

\(\Rightarrow\left[{}\begin{matrix}x-2=0\\3x-1=0\end{matrix}\right.\)

\(\Rightarrow\left[{}\begin{matrix}x=2\\x=\dfrac{1}{3}\end{matrix}\right.\)

\(b,x^2+5x+4=0\)

\(\Rightarrow x^2+4x+x+4=0\)

\(\Rightarrow\left(x^2+4x\right)+\left(x+4\right)=0\)

\(\Rightarrow x\left(x+4\right)+\left(x+4\right)=0\)

\(\Rightarrow\left(x+4\right)\left(x+1\right)=0\)

\(\Rightarrow\left[{}\begin{matrix}x+4=0\\x+1=0\end{matrix}\right.\)

\(\Rightarrow\left[{}\begin{matrix}x=-4\\x=-1\end{matrix}\right.\)

Bình luận (0)
AT
16 tháng 11 2017 lúc 19:50

a) \(3x\left(x-2\right)-x+2=0\)

\(\Rightarrow3x\left(x-2\right)-\left(x-2\right)=0\)

\(\Rightarrow\left(x-2\right)\left(3x-1\right)=0\)

\(\Rightarrow\left\{{}\begin{matrix}x-2=0\\3x-1=0\end{matrix}\right.\)

\(\Rightarrow\left\{{}\begin{matrix}x=2\\x=\dfrac{1}{3}\end{matrix}\right.\)

Vậy ...

b) \(x^2+5x+4=0\)

\(\Rightarrow x^2+4x+x+4=0\)

\(\Rightarrow x\left(x+4\right)+\left(x+4\right)=0\)

\(\Rightarrow\left(x+4\right)\left(x+1\right)=0\)

\(\Rightarrow\left\{{}\begin{matrix}x+4=0\\x+1=0\end{matrix}\right.\)

\(\Rightarrow\left\{{}\begin{matrix}x=-4\\x==-1\end{matrix}\right.\)

Vậy ...

Bình luận (1)
DH
16 tháng 11 2017 lúc 19:52

a) 3x ( x - 2 ) - x + 2 = 0

=> 3x ( x - 2 ) - ( x - 2) = 0

=> ( x - 2 ) ( 3x - 1 ) = 0

=> x - 2 = 0

3x - 1 = 0

=> x = 2

x = \(\dfrac{1}{3}\)

b) \(x^2+5x+4\)= 0

=> \(x^2+x+4x+4=0\)

=> x ( x + 1 ) + 4 ( x + 1 ) = 0

=> ( x + 1 ) ( x + 4 ) = 0

=> x + 1 = 0

x + 4 = 0

=> x = -1

x = -4

Bình luận (0)

Các câu hỏi tương tự
DN
Xem chi tiết
DH
Xem chi tiết
BA
Xem chi tiết
NS
Xem chi tiết
LL
Xem chi tiết
CG
Xem chi tiết
TN
Xem chi tiết
LS
Xem chi tiết
HY
Xem chi tiết